PENINGKATAN KETERAMPILAN MENULIS PUISI DENGAN MEDIA GAMBAR BAGI SISWA KELAS III SD - Saragih, Jenni Herdina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This article aims to express and describre increase skill of write poetry whit use picture mediation for the third class of 09 Bahagia Panti Elemtery School. This type of  research used Research Action Class (PTK) method whit aproach qualitative and quantitative. Research obyect is potry, data collection is done through observation, space note, documentation and work result of many kinds poetry. Data analysis was done from planing, execution, inspection, unitl reflection and conclude. This data reduction based on problem research, data ready, and conclude or verivication. The results showed that the use picture media can increase skill to write a poetry for the third class of 09 Bahagia Panti Elemtery School. Kata kunci : menulis puisi, media gambar, dan siswa kelas iii sd